961. ZINGIBER FLAVOFUSIFORME: Zingiberaceae. (22nd February 2021) - Tanaka, Nobuyuki; Aung, Mu Mu
Summary: Zingiber flavofusiforme M.M. Aung & Nob. Tanaka, a little‐known species, is described and illustrated. This species was described as endemic to Myanmar, but has recently been recorded from Assam, India. Morphological comparison with the Indian plants and variation in this species is discussed. An overview of Hthamanthi Wildlife Sanctuary, the type locality of this species, is introduced.